Efficacy, usability and sequence of operations of a workflow‐integrated algorithm for basal–bolus insulin therapy in hospitalized type 2 diabetes patients. Issue 2 (29th August 2013) - Mader, J. K.; Neubauer, K. M.; Schaupp, L.; Augustin, T.; Beck, P.; Spat, S.; Höll, B.; Treiber, G. M.; Fruhwald, F. M.; Pieber, T. R.; Plank, J.
<x xml:space="preserve">Abstract</x> Aims To evaluate glycaemic control and usability of a workflow‐integrated algorithm for basal–bolus insulin therapy in a proof‐of‐concept study to develop a decision support system in hospitalized patients with type 2 diabetes. Methods In this ward‐controlled study, 74 type 2 diabetes patients (24 female, age 68 ± 11 years, HbA1c 8.7 ± 2.4% and body mass index 30 ± 7) were assigned to either algorithm‐based treatment with a basal–bolus insulin therapy or to standard glycaemic management. Algorithm performance was assessed by continuous glucose monitoring and staff's adherence to algorithm‐calculated insulin dose. Results Average blood glucose levels (mmol/l) in the algorithm group were significantly reduced from 11.3 ± 3.6 (baseline) to 8.2 ± 1.8 (last 24 h) over a period of 7.5 ± 4.6 days (p < 0.001). The algorithm group had a significantly higher percentage of glucose levels in the ranges from 5.6 to 7.8 mmol/l (target range) and 3.9 to 10.0 mmol/l compared with the standard group (33 vs. 23% and 73 vs. 53%, both p < 0.001). Physicians' adherence to the algorithm‐calculated total daily insulin dose was 95% and nurses' adherence to inject the algorithm‐calculated basal and bolus insulin doses was high (98 and 93%, respectively). In the algorithm group, significantly more glucose values <3.9 mmol/l were detected in the afternoon relative to other times (p < 0.05), a finding mainly related to pronounced morning glucose excursions and requirements for corrective bolus insulin at lunch. Conclusions The workflow‐integrated algorithm for basal–bolus therapy was effective in establishing glycaemic control and was well accepted by medical staff. Our findings support the implementation of the algorithm in an electronic decision support system.